We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
161
4
avatar

\(Suppose that $g(x)=f^{-1}(x)$. If $g(-15)=0$, $g(0)=3$, $g(3)=9$ and $g(9)=20$, what is $f(f(9))$?\)

 Jun 15, 2019
 #1
avatar+8810 
+3

Suppose that   g(x) = f-1(x) .  If   g(-15) = 0 ,  g(0) = 3 ,  g(3) = 9   and   g(9) = 20 ,  what is   f( f(9) ) ?

 

If     g(x) = f-1(x)     then we can take  f  of both sides of the equation to get     f( g(x) )  =  x

 

Since  f( g(x) )  =  x  ,

 

f( g(3) )  =  3

                        And we know   g(3)  =  9   so we can substitute  9  in for  g(3)

f( 9 )  =  3

 

Again since  f( g(x) )  =  x  ,

 

f( g(0) )  =  0

                        And we know   g(0)  =  3   so we can substitute  3  in for  g(0)

f( 3 )  =  0

 

So we have found....

 

f( f(9) )   =  f( 3 )  =  0

 Jun 15, 2019
 #2
avatar
+1

\(Tysm\)

Guest Jun 15, 2019
 #4
avatar+23354 
+4

 Please help! Do not know hot to solve

 

\(\begin{array}{|rcl|rcl|} \hline g(x) &&& f(x)&=&g^{-1}(x) \\ \hline g(-15)&=&0 & f(0)&=&-15 \\ g(0)&=&3 & f(3) &=& 0 \\ g(3)&=&9 & f(9) &=& 3 \\ g(9)&=&20 & f(20) &=& 9 \\ \hline \end{array} \)

 

\(\mathbf{f(f(9))} = f(3) \mathbf{= 0} \)

 

laugh

 Jun 17, 2019

3 Online Users